Develop a weight detection unit of the glass collection machine with reward system - Khairul Azri, Ngadimen (2012)
Nowadays glass had become some of the solid waste produce by the society. Glass is primary ingredient for window, bottle, or as container to store for consumer and can be glass water for drinking. Glass had its unique property of material because it can be recycle after use it, and for the recycle process its only need 40% of energy required from the virgin material to produce a new glass. Awareness in the consumer about recycling is still low, it because glass recycling in Malaysia is still in its infancy. Less than 30% of new bottles are made from recycled glass compared to 80% in Thailand and 60-70% in Europe. A vast majority of glass still ends up at landfills (MPK, 2009). This project is about design and fabrication of weight detection unit that can detect glass weight and convert weight to bonus point. It has advantage because it is independently weight detector that can be used to detect any weight and can be attach to any machine. As the conclusion, this project had achieves its entire objective successfully. This project was done around thirteen week included almost all steps of the report such as design, analysis, fabrication process and others.